Tracing the Non-Aligned Architecture: Environments of Technical Cooperation and the Work of Croatian Architects in Kumasi, Ghana (1961-1970) - Smode Cvitanovic, Mojca (Histories of Postwar Architecture, 2020)
Focusing on the work of a group of Croatian i.e. Yugoslav architects in Ghana, the paper explains the nature of technical cooperation as a model of temporary international contract work in relation to the specificities of the environment built consequently. It focuses on the engagement of Miro Marasović as the head of the Kwame Nkrumah University of Science and Technology Development Office from 1961 to 1964. As its contextual framework, the paper addresses bilateral technical cooperation as a form of international communication and exchange, the practices of the Non-Aligned Movement, and the interrelations of the pre- and post-independence generation of modern architecture in Africa.